PROJECT MANAGEMENT MATURITY AND PROJECT MANAGEMENT SUCCESS IN THE ENGINEERING AND CONSTRUCTION INDUSTRIES IN SOUTHERN AFRICA - Pretorius, S; Steyn, H; Jordaan, JC (The South African Journal of Industrial Engineering, 2012)
Previous studies have attempted to determine how the success of South African IT projects related to the project management maturity of the organisations that executed the projects. The study reported in this article was conducted during 2010 in the engineering and construction sectors. This paper reports on a structured questionnaire distributed to 1,625 individuals mainly in the South African engineering and construction industries, from which 255 responses were received.